Aplikasi Skyflash Tricking Academy Sebagai Media Latihan Olahraga Tricking pada Siswa Ekstrakurikuler SMK Darussalam Karangpucung - Azis, Farhan Nur; Kusmiyati, Kusmiyati; Saefulah, Dian Imam (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop and test the feasibility of the Skyflash Tricking Academy application as a training media for the sport of tricking for extracurricular students at SMK Darussalam Karangpucung. The method used is Research and Development (R&D) with a simplified Borg & Gall model. This application contains tricking material from basic to advanced levels, complete with videos, photos of the steps, and supporting theories. The research sample is determined using a multistage sampling technique with a snowball pattern. Each stage of field testing uses different samples. The operational field trial is the final development testing phase that uses a larger sample size than the initial and main field trials. This research and development use descriptive data analysis techniques. The results of the validation and trials indicate that this application is feasible to use and can enhance students' motivation and skills in tricking practice.